2016
DOI: 10.1249/01.mss.0000487274.37735.33
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Sedentary Time and Physical Activity in University Office Workers

Abstract: Regular exercise and physical activity (PA) reduce the risk of chronic disease and premature mortality. Emerging evidence links sedentary behaviors, independent of exercise and PA, with increased risk of disease and premature mortality. Sedentary behaviors include sitting or lying during waking hours. Many adults spend the majority of time in sedentary occupations. PURPOSE: To determine, in sedentary office workers: 1) time spent in PA and sedentary behaviors and 2) whether the workers who were most active als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, a recent study by Cooper and Barton (2016) revealed that almost half of their surveyed adult university employees reported insufficient PA based on the recommended activity guidelines. Physical inactivity is a modifiable risk factor for a range of chronic diseases and conditions diseases, including cardiovascular disease and obesity, and prolonged sitting is an independent risk factor for low back pain, neck pain, and premature mortality (Larouere, Urda, & Lynn, 2016; Matthews et al, 2012).…”
mentioning
confidence: 99%
“…For example, a recent study by Cooper and Barton (2016) revealed that almost half of their surveyed adult university employees reported insufficient PA based on the recommended activity guidelines. Physical inactivity is a modifiable risk factor for a range of chronic diseases and conditions diseases, including cardiovascular disease and obesity, and prolonged sitting is an independent risk factor for low back pain, neck pain, and premature mortality (Larouere, Urda, & Lynn, 2016; Matthews et al, 2012).…”
mentioning
confidence: 99%